OPTIMALISASI PRODUKSI DAN TATA KELOLA KEUANGAN MELALUI PENERAPAN MESIN PUNCH ROLL DIES DAN APLIKASI DIGITAL PADA UMKM J&R DESA DUWET - Muhammad Akhlis Rizza; Evi Suwarni; Galuh Zuhria Kautzar (Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aims to improve the production capacity and financial management of J&R MSME, a cassava chips producer in Duwet Village, Tumpang District, Malang Regency. The main problems faced by the partner are limited production capacity due to manual processes and simple, unorganized financial records. The solutions offered include the implementation of a punch roll dies machine to shorten the production chain and the adoption of digital financial management using the Teman Bisnis application. The methods applied consist of socialization, training, technology implementation, mentoring, and evaluation. The results of the activity show an increase in production capacity from 200 kg/day to 250–300 kg/day, as well as improved financial recording with more than 80% of transactions recorded digitally. This program has had a positive impact on productivity, financial transparency, and the potential for job creation in Duwet Village.